Peran Pemerintah Daerah dan Pokdarwis dalam Pengembangan Objek Wisata Air Terjun Curug Lestari di Kabupaten Lampung Tengah - Yuni Ratna Sari; Fajrelia Safaatul Khasanah (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2022)
Tourism as one of the potential sources to be able to improve the economy and community welfare through activities in the form of managing and utilizing the potential of tourist attractions, there is an important element of concern in the development of tourism, namely the role of parties who have an interest in tourism, namely local governments and tourism-conscious community groups. Local governments and tourist conscious groups (pokdarwis) are the main keys to how a tourist attraction can progress and develop well if these two parties can implement their role to the maximum. The problem that will be studied in this study is related to how the role of local governments and tourism conscious groups in developing Curug Lestari waterfall attractions. This research is qualitative research with a descriptive approach with data collection techniques, namely observation, interview and documentation. Based on research that has been done it was found that local governments and pokdarwis have not been able to fully contribute and carry out their roles for the development of Curug Lestari tourist attractions. This leads to the development of Curug Lestari tourist attractions both in terms of development, improvement of road infrastructure, not been seen well. The existence of obstacle factors experienced by both parties is also the cause of the lack of maximum implementation of their role.